Progress in TILLING as a tool for functional genomics and improvement of crops - Chen, Liang; Hao, Liugen; Parry, Martin A. J; Phillips, Andrew L; Hu, Yin‐Gang (Journal of integrative plant biology, 2014)
Food security is a global concern and substantial yield increases in crops are required to feed the growing world population. Mutagenesis is an important tool in crop improvement and is free of the regulatory restrictions imposed on genetically modified organisms. Targeting Induced Local Lesions in Genomes（TILLING）, which combines traditional chemical mutagenesis with high‐throughput genome‐wide screening for point mutations in desired genes, offers a powerful way to create novel mutant alleles for both functional genomics and improvement of crops. TILLING is generally applicable to genomes whether small or large, diploid or evenallohexaploid, and shows great potential to address the major challenge of linking sequence information to the function of genes and to modulate key traits for plant breeding. TILLING has been successfully applied in many crop species and recent progress in TILLING is summarized below, especially on the developments in mutation detection technology, application of TILLING in gene functional studies and crop breeding. The potential of TILLING/EcoTILLING for functional genetics and crop improvement is also discussed. Furthermore, a small‐scale forward strategy including backcross and selfing was conducted to release the potential mutant phenotypes masked in M2（or M3） plants.